Simplifying Stem Cell Therapy for IRs: Exploring New Horizons in Interventional Radiology and Cell Therapy - Hossein Ghanaati; Maedeh Rouzbahani (The Arab Journal of Interventional Radiology)
The effective treatment of various diseases requires not only medications but also precise delivery methods to the body and specific organs. In this regard, radiology plays a crucial role, acting as the eyes of physicians. In contrast, interventional radiology serves as its hands, acting as one of the most effective drug delivery systems. Among interventional radiology disciplines, arterial drug delivery through arteries holds paramount importance as organs primarily receive nourishment directly from them. Furthermore, regenerative medicine is a burgeoning field dedicated to repairing diverse body tissues without relying on pharmaceutical drugs. Stem cells, inherent in various parts of our bodies, are vital for tissue regeneration and reconstruction. Depending on the treatment approach, stem cells can be sourced from the patient's body (autologous) or another individual (allogeneic). There exist various types of stem cells across species, with regenerative properties observed in animals and even plants. However, targeted cell therapy is preferred over systematic injections throughout the body for better efficacy. This article aims to familiarize interventionalists with stem cells and provide them with a clear and helpful explanation of their functions, mechanisms of action, different sources, and other relevant aspects. This will help them select the most appropriate cells for their therapeutic purposes. By comprehensively understanding the significance of stem cells in interventional radiology, we can implement optimal methodologies to address diverse medical conditions efficiently.